(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2024)
Objective: Rabies is a real risk to public health, and remains a zoonosis with considerable medical and economic impact on both humans and animals. The aim of this study was to identify and evaluate rabies control measures applied in the urban township of Dalaba. Materials and Methods: The methodology adopted was based on consultation of animal health managers and analysis of archives; field surveys of human health services, owner-managers of domestic carnivores and livestock breeders; and evaluation of anti-epizootic measures. Results: From 2010 to 2017, consultation of executives and analysis of archives revealed the following data: 25 reported cases of carnivore bites, of which 19 were observed by veterinary practitioners; 32 cases of clinical animal rabies recorded, including 18 dogs, 13 cattle and 1 cat; and 103 animal rabies vaccinations. A search of health facility consultation registers showed 400 cases of bites attributable to carnivores, of which 37 victims were subjected to post-exposure vaccination. From 112 carnivore owners surveyed, (50.89%) claimed to be perfectly aware of the disease. To prevent the disease, 14.28% have their animals caged; 22.32% vaccinate and 29.82% vaccinate regularly; 14.29% have their dogs castrated, and 31.25% feed their animals regularly. Among the 210 carnivores registered, 45 dogs (21.43%) and 2 cats (0.95%) have been vaccinated against rabies, giving a vaccination coverage rate of 22.38%. Conclusion: At the end of this research, we noted that rabies constitutes a real threat and a major zoonosis requiring the adoption of strategies for better control.